Current, emerging, and potential therapies for non-alcoholic steatohepatitis - Yang, Zhen; Wang, Lin (Frontiers in Pharmacology, 2023)
Non-alcoholic fatty liver disease (NAFLD) has been identified as the most common chronic liver disease worldwide, with a growing incidence. NAFLD is considered the hepatic manifestation of a metabolic syndrome that emerges from multiple factors (e.g., oxidative stress, metabolic disorders, endoplasmic reticulum stress, cell death, and inflammation). Non-alcoholic steatohepatitis (NASH), an advanced form of NAFLD, has been reported to be a leading cause of cirrhosis and hepatic carcinoma, and it is progressing rapidly. Since there is no approved pharmacotherapy for NASH, a considerable number of therapeutic targets have emerged with the deepening of the research on NASH pathogenesis. In this study, the therapeutic potential and properties of regulating metabolism, the gut microbiome, antioxidant, microRNA, inhibiting apoptosis, targeting ferroptosis, and stem cell-based therapy in NASH are reviewed and evaluated. Since the single-drug treatment of NASH is affected by individual heterogeneous responses and side effects, it is imperative to precisely carry out targeted therapy with low toxicity. Lastly, targeted therapeutic agent delivery based on exosomes is proposed in this study, such that drugs with different mechanisms can be incorporated to generate high-efficiency and low-toxicity individualized medicine.